A Study on the Proactive Disclosure in Local Government Websites in Nepal - Dongol, Nikhil (Kathmandu School of Law Review, 2021)
Access to Information of a citizen is an essential aspect of democracy. It is taken as a fundamental right of a citizen and a necessary precursor of a responsible, transparent and accountable government to maintain rule of law in a country both politically as well as economically. There are essentially three stakeholders in access to information viz. demand-side general peoples, supply-side public entity, and various organizations as facilitators. Realizing this crucial interplay between citizen, public entity, and access to information, this paper explores various laws, jurisprudence, and practices to enhance the general understanding on the demand side. This paper analyses the websites of 17 local governments (metropolitan and sub-metropolitan cities) of Nepal in relation to legally mandated 20 indicators of proactive disclosure of Access to Information. However, this paper does not attempt to provide a blueprint for implementation of the policies of Access to Information due to the diversity of situations in different governance rather would highlight the present condition of proactive disclosure, loopholes, and the ways that can enhance the disclosure practices in local governments in Nepal.